Has the time really come for universal videolaryngoscopy?. (October 2022) - Cook, Tim M.; Aziz, Michael F.
Summary: Recent evidence, highlighted in this editorial, creates a strong argument for universal use of videolaryngoscopy in anaesthesia to improve efficiency and safety of tracheal intubation. In a recent study published in the British Journal of Anaesthesia, the authors implemented widespread (66%) use of videolaryngoscopy as first choice in one hospital and compared this with a control hospital, in which this was not implemented. Increased videolaryngoscopy use was associated with a significant fall in the rate of difficult airways, use of airway rescue techniques, and operator-reported difficulty, whilst in the control hospitals no such changes were seen. Locations outside the operating theatre might also benefit from universal laryngoscopy, but the evidence base is less robust, most notably in pre-hospital emergency medicine. The extent to which variation in results in different locations is attributable to different patient factors or organisational and operator factors is considered.